An Italian prospective multicenter study on colonoscopy practice and quality: What has changed in the last 10 years. Issue 1 (January 2023) - Testoni, Pier Alberto; Notaristefano, Chiara; Soncini, Marco; Hassan, Cesare; Monica, Fabio; Radaelli, Franco; Triossi, Omero; Pasquale, Luigi; Neri, Matteo; Cannizzaro, Renato; Leandro, Gioacchino; ,; et al.
Abstract: Background: A relevant number of adenomas can be missed during colonoscopy. Aims: Assess the current status of colonoscopy procedures in Italian centers. Methods: A prospective observational study involving 17 hospitals (34 endoscopists) included consecutive patients undergoing standard colonoscopy. In the first phase, endoscopists performed consecutive colonoscopies. In the second phase, retraining via an online learning platform was planned, while in the third phase data were collected analogously to phase 1. Results: A total of 3, 504 patients were enrolled. Overall, a BBPS score ≥6 was obtained in 95.6% of cases (94.8% and 96.9% in the pre- and post-training phases, respectively). 88.4% of colonoscopies had a withdrawal time ≥6 min (88.2% and 88.7% in the pre- and post-training phases). Median adenoma detection rate (ADR) was 39.1%, with no significant differences between the pre- and post-training phases (40.1% vs 36.9%; P  = 0.83). In total, 81% of endoscopists had a ADR performance above the 25% threshold. Conclusion: High colonoscopy quality standards are achieved by the Italian hospitals involved. Quality improvement initiatives and repeated module-based colonoscopy-training have been promoted in Italy during the last decade, which appear to have had a significant impact on quality colonoscopy metrics together with the activation of colorectal cancer screening programs.